Diffusing alpha-emitters radiation therapy in combination with temozolomide or bevacizumab in human glioblastoma multiforme xenografts - Nishri, Yossi; Vatarescu, Maayan; Luz, Ishai; Epstein, Lior; Dumančić, Mirta; Del Mare, Sara; Shai, Amit; Schmidt, Michael; Deutsch, Lisa; Den, Robert B.; Kelson, Itzhak; Keisari, Yona; et al. (Frontiers in Oncology, 2022)
Glioblastoma multiforme (GBM) is at present an incurable disease with a 5-year survival rate of 5.5%, despite improvements in treatment modalities such as surgery, radiation therapy, chemotherapy (e.g., Temozolomide, TMZ), and targeted therapy (e.g., the antiangiogenic agent Bevacizumab, BEV). Diffusing Alpha-emitters Radiation Therapy (DaRT) is a new modality which employs radium-224-loaded seeds that disperse alpha-emitting atoms inside the tumor. This treatment was shown effective in mice bearing human-derived GBM tumors. Here, the effect of DaRT in combination with standard-of-care therapies such as TMZ or BEV was investigated. In a viability assay, the combination of alpha radiation with TMZ doubled the cytotoxic effect of each of the treatments alone in U87 cultured cells. A colony formation assay demonstrated that the surviving fraction of U87 cells treated by TMZ in combination with alpha irradiation was lower than was achieved by alpha- or x-ray irradiation as monotherapies, or by x-ray combined with TMZ. The treatment of U87-bearing mice with DaRT and TMZ delayed tumor development more than the monotherapies. Unlike other radiation types, alpha radiation did not increase VEGF secretion from U87 cells in culture. BEV treatment introduced several days after DaRT implantation improved tumor control, compared to BEV or DaRT as monotherapies. The combination was also shown to be superior when starting BEV administration prior to DaRT implantation in tumors large relative to the seed size. BEV induced a decrease in CD31 staining under DaRT treatment, increased the diffusive spread of 224Ra progeny atoms in the tumor tissue, and decreased their clearance from the tumor through the blood. Taken together, the combinations of DaRT with standard-of-care chemotherapy or antiangiogenic therapy are promising approaches, which may improve the treatment of GBM patients.